Neonatal Simulation Program: A 5 Years Educational Journey From Qatar - Mohammad A. A. Bayoumi (17993782) (2022)
We describe the process of implementation, adaptation, expansion and some related clinical intuitional impacts of the neonatal simulation program since its launch in 2016 in a non-simulation neonatal unit. The team has developed 6 types of curricula: 1 full-day course and 5 half-day workshops. A total of 35 free of charge simulation courses/workshops were conducted, 32 in Qatar and 3 abroad with a total of 799 diverse participants. There was a steady increase in the overall success rate of PICC insertion from 81.7% (309/378) to 97.6% (439/450) across 3 years (P < 0.0001). The first attempt PICC insertion success rate has been also increased from 57.7% (218/378) to 66.9% (301/450) across 3 years. The mean duration of PICC insertion has been improved from 39.7 ± 25 to 34.9 ± 12.4 min after implementing the program (P = 0.33). The mean duration of the LISA catheter insertion at the beginning of the workshop was 23.5 ± 15.9 compared to 12.1 ± 8.5 s at the end of the workshop (P = 0.001). When it came to clinical practise in real patients by the same participants, the overall LISA catheter insertion success rate was 100% and the first attempt success rate was 80.4%. The mean duration of LISA catheter insertion in real patients was 26.9 ± 13.9 s compared to the end of the workshop (P = 0.001). The mean duration of the endotracheal intubation at the beginning of the workshop was 12.5 ± 9.2 compared to 4.2 ± 3.8 s at the end of the workshop (P = 0.001). In real patients, the first-attempt intubation success rate has been improved from 37/139 (26.6%) in the first year to 141/187 (75.5%) in the second year after the program implementation (P = 0.001). The mean duration of successful endotracheal intubation attempts has been improved from 39.1 ± 52.4 to 20.1 ± 9.9 s (P = 0.78). As per the participants, the skills learned in the program sessions help in protecting neonates from potential harm and improve the overall neonatal outcome. Implementing a neonatal simulation program is a promising and feasible idea. Our experience can be generalised and replicated in other neonatal care institutions. Other Information Published in: Frontiers in Pediatrics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fped.2022.843147